Robotics and Well-Being - Aldinhas Ferreira, Maria Isabel; Silva Sequeira, João.; Singh Virk, Gurvinder; Tokhi, Mohammad Osman; E. Kadar, Endre; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights some of the most pressing safety, ethical, legal and societal issues related to the diverse contexts in which robotic technologies apply. Focusing on the essential concept of well-being, it addresses topics that are fundamental not only for research, but also for industry and end-users, discussing the challenges in a wide variety of applications, including domestic robots, autonomous manufacturing, personal care robots and drones.
1. Technological Development and Well-Being -- 2. The IEEE Global Initiative on Ethics of Autonomous and Intelligent -- 3. Humans and Robots: A New Social Order in Perspective? -- 4. Game Theory Formulation for Ethical Decision Making -- 5. Beyond the Doctrine of Double Effect: A Formal Model of True Self-Sacriﬁce -- 6. Mind the Gap: A Theory is Needed to Bridge the Gap Between the Human Skills and Self-Driving Cars -- 7. Who should you sue when no-one is behind the wheel? Difﬁculties in establishing new norms for autonomous vehicles in the European Union -- 8. Robotics, Big Data, Ethics and data protection: a matter of approach -- 9. The concept of friendliness in robotics: ethical challenges -- 10. Ethics, the only safeguard against the possible negative impacts of autonomous robots? -- 11. AI in the Sky: How People Morally Evaluate Human and Machine Decisions in a Lethal Strike Dilemma -- 12. Putting people and robotstogether in manufacturing: are we ready? -- 13. A Survey On The Pain Threshold And Its Use In Robotics Safety Standards -- 14. Lisbon Robotics Cluster: Vision and Goals -- 15. Index.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Ethics; User interfaces (Computer systems).; Human-computer interaction; Security systems; Control, Robotics, Automation; Artificial Intelligence; Moral Philosophy and Applied Ethics; User Interfaces and Human Computer Interaction; Security Science and Technology